Significance of tests for petroleum products - Rand, Salvatore J., 1933-; Verstuyft, Allen W., 1948- (ASTM International, 2018)
"Technology and ASTM International are undergoing accelerating change. To quote Charles Darwin, "It is not the strongest of the species that survives, nor the most intelligent that survives. It is the one that is the most adaptable to change." Analytical method standards are often available from ASTM International within weeks of their being voted on for approval. The response of the various committees of ASTM International to new developments and emerging needs in the industrial and petroleum fuels and lubricants as well as alternate fuel industries, and to unexpected occurrences in the field, is both swift and focused. It is because of this unprecedented and exponential increase in new testing methods that Manual 1 is being revised only seven years following its prior publication"-- Provided by publisher.
"ASTM Stock Number: MNL1-9th edition."
Keywords: Petroleum -- Testing.; Petroleum products -- Testing.; elektronické knihy; electronic books